Design and Implementation of Grounding System for 100 kWP On-Grid Solar Power Plant in Pamulang University Environment - Darmawan, Yusron Dwi; Rozak, Ojak Abdul; Triyanto, Aripin (Program Studi Teknik Elektro Universitas Khairun, 2025)
The grounding system in a Solar Power Plant installation has an important role as a safeguard against external disturbances such as overcurrent and overvoltage due to lightning strikes or internal disturbances. Considering that solar modules are installed in open areas and at certain heights, the grounding system is crucial to protect equipment and personnel. This study discusses the design of a 100 kWp On-Grid PLTS grounding system at Pamulang University, including external lightning rod planning using the Early Streamer Emission (ESE) method with the NFC 17-102 standard and the rolling sphere calculation method based on IEC 62305-3. The calculation results show that the lightning rod protection radius in building B is 117.79 meters with a lightning rod height of 6 meters. The initial grounding resistance value of 11.6 Ω was obtained from a single vertical electrode 3 meters deep. To achieve a resistance value below 5 Ω according to the PUIL 2011 standard, equipotential bonding between floors and between electrodes is required. This research is expected to be a reference in designing lightning protection and grounding systems for PLTS installations in the Pamulang University environment.